An exploratory study examining spurious loyalty within the South African short-term insurance industry - Human, Catharine (The IIE, 2018)
This explorative study was undertaken to provide insight into which social norms and situational factors explain spurious loyalty towards OUTsurance. This study outlined how the increase in VAT is expected to erode the disposable income of household within South Africa and thereby, increase the policy lapse rate of insurers (PWC, 2016). Thus, it is important for South African short-term insurance companies to place greater focus on strengthening the firm-consumer relationship in order to retain their current customers (Strachan & Roberts- Lombard, 2011). Since limited studies have focused on spurious loyalty in a South African context, this study fills this gap by focusing on the concept of spurious loyalty and the factors of spurious loyalty to assist short term insurers in comprehending how to build and cultivate strong ﬁrm-customer relationships (Ndubisi,, Malhotra, & Wah, 2009) loyalty. The data used in this research study was acquired from six semi-structured interviews conducted in Pretoria, South Africa, with OUTsurance policy holders, between the ages of 45 – 55 and who could give a personal account of their relationship with the brand. A thematic content analysis was used for transcribing and codding the semi-structured interviews into three categories and then further into themes derived from the key notions and sentiments of each participant.
Keywords: Relationship marketing; Customer loyalty; Spurious loyalty; Social norms; Brands